Platelet Rich Fibrin as Wound Coverage of Donor Site in Free Gingival Graft - Agrawal, Shweta; Koirala, Pramod Kumar; Pradhan, Shalini; Gorkhali, Ranjita Shrestha (Journal of Nepalese Society of Periodontology and Oral Implantology, 2018)
Free gingival graft is one of the technique used for root coverage so as to increase the inadequate keratinized tissue. The donor tissue is most frequently taken from the palate and generally the donor site is not covered or protected. Platelet rich fibrin is one of the good option for the wound coverage of donor site after free gingival graft so as to reduce the pain perception to patient and faster wound healing. The case report includes two cases with gingival recession, treated on the same day with free gingival graft with the use of platelet rich fibrin in the donor site in case 1 and without platelet rich fibrin in case 2 respectively which were compared for pain perception and wound healing postoperatively at 24 hours, 3 days, 5 days, 7 days and 14 days. There was less pain perception and discomfort in the donor site with the use of platelet rich fibrin and enhanced healing compared to donor site without platelet rich fibrin.